A facet measure of money madness: A preliminary analyses of a new questionnaire. Issue 3 (20th October 2021) - Furnham, Adrian; Horne, George
Abstract: This study reports on the development of a new, facet level questionnaire to measure "money madness" based on a well‐established, four‐factor model. It reviews the papers currently available to researchers on those with "money troubles" such as financial distress. In this study, 256 adult participants from diverse backgrounds, who were recruited online, completed a 52‐item questionnaire designed to measure three facets of each of the four money factors: Security, Power, Love, and Freedom. They also completed a financial literacy questionnaire which had two factors. The internal reliability of the four money factors was satisfactory but this was not the case for all the facets. Factor analysis partly confirmed the hypothesized structure. Regressions indicated that associating money with power was the best predictor of financial literacy. The use of a facet or factor measure and necessary future theoretical and psychometric developments are discussed.